Cytokine Storm in COVID 19 Culminating in Candida Endocarditis. Issue 1 (June 2021) - Kaneria, Mala Vinod; Budhe, Abhijeet; Lade, Prasenjit; Poyekar, Tejas
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), had made its demonic debut on the world stage in December 2019 and has been sweeping across the globe since then. 1 This new kid on the block soon also joined the cluster of risk factors, leading to fungal infections. Cases of mucormycosis, colloquially called "black fungus, " (COVID-19 associated mucormycosis [CAM]), had escalated in India, and the focus then shifted to Candida, the so-called "white fungus." The dysregulated immune system in COVID-19, along with the immunosuppressants used to treat it, may give rise to fatal secondary infections. We present a patient who had a stormy, prolonged course following COVID-19, with multiple bacterial and viral infections, subsequently culminating in fungal endocarditis with Candida tropicalis .